The Differential Effect of First‐Time Single‐Point Cane Use between Healthy Young and Older Adults. Issue 12 (2nd April 2021) - Omana, Humberto; Madou, Edward; Divine, Alison; Wittich, Walter; Hill, Keith D.; Johnson, Andrew M.; Holmes, Jeffrey D.; Hunter, Susan W.
Abstract: Background: Walking aids are often introduced to older adults to enable independent mobility. Single‐point canes are the most common device used. Benefits are tempered by research suggesting that walking aids increase fall risk. A better understanding of the effect of walking aid use on gait performance is required. Objective: To evaluate differences in the effect of initial single‐point cane use on gait between younger (YAs) and older adults (OAs). Design: Cross‐sectional. Setting: Community‐dwelling. Participants: Twenty‐six YAs (mean age ± standard deviation [SD]: 23.7 ± 2.8 years) and 25 OAs (mean age ± SD: 70.8 ± 14.1 years) participated. Inclusion criteria were 18 to 35 years of age for YAs or ≥50 years for OAs, be able to ambulate unassisted, and without any condition affecting mobility. Interventions: Not applicable. Main Outcome Measure(s): Gait velocity and stride time variability under different walking path configurations (straight path, Groningen Meander Walking Test, Figure‐of‐8 Walk Test) and conditions (unassisted walking, walking with a single‐point cane, and walking with a single‐point cane while completing a cognitive task) were recorded in a laboratory. The arithmetic task of subtracting 1s from 100 was used as the secondary cognitive task. Data analysis included separate three‐way mixed analyses of variance (ANOVAs; path/condition/group). Results: There was a statistically significant two‐way interaction between walking path and condition for velocity ( P  < .001, ω 2  = 0.03) and stride time variability ( P  = .032, ω 2  = 0.02). In addition, a significant main effect of group was also observed (velocity: P  = .004, ω 2  = 0.07; stride time variability: P  = .001, ω 2  = 0.09). Conclusions: Using a single‐point cane decreased velocity and increased stride time variability in both YAs and OAs. However, the cognitive load and effect on gait of initial cane use was not different between age groups. Standardized guidelines aimed at facilitating a clientʼs transition toward the safe use of a walking aid are needed. Future research should evaluate if training can mitigate some of the adverse changes to gait stability observed with initial walking aid use.